ENHANCING HIGH-SPEED PERFORMANCE: MODIFICATION OF BOOM BARRIER GATE WITH PUSH BRAKING SYSTEM FOR ETC APPLICATION - Nafis, Muhammad Luthfi; Pranoto, Hadi; Youlia, Rikko Putra (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2023)
Congestion at toll roads has become a pervasive issue in contemporary times, predominantly manifesting at toll booths during the payment process. A noteworthy contributor to this congestion has been identified as the sluggish operational speed of boom gates. In response to this challenge, a modification strategy was implemented to enhance the operational efficiency of existing boom gates. The primary modification involved substituting the conventional electric motor with a more advanced Brushless DC (BLDC) motor boasting a power rating of 660 watts. Additionally, an innovative augmentation integrated a motorcycle disk brake system into the boom gate mechanism. Replacing the original electric motor's internal brake system with the disk brake system aimed to optimize the overall performance of the boom gate. The integration of the motorcycle disk brake system was further complemented by incorporating the push braking system (knoken braking system), serving as the actuator instead of the traditional motorcycle lever handle. This strategic substitution was instrumental in activating the disk brake function at the boom gate. During peak rush hours, the modified boom gate underwent rigorous testing at both the Ciawi and Kelapa Gading toll gates. Results from the trial activities unveiled a remarkable improvement in the boom gate's operational speed. Specifically, the opening speed demonstrated an impressive surge of 51 percent, catapulting from 548 ms to 265 ms. Similarly, the closing speed exhibited a commendable enhancement of 44 percent, elevating from 602 ms to 332 ms. Furthermore, the boom gate cycle per hour experienced a notable escalation, increasing by 25 percent from 356 to 449 cars per hour. These findings underscore the efficacy of the implemented modifications in ameliorating congestion issues at toll booths.